Ketidaksetaraan Gender Dalam Pengelolaan Sumber Daya Laut: Studi Kasus Pada Masyarakat Pesisir Di Desa Torobulu Kecamatan. Laeya, Kabupaten Konawe Selatan - Syaifudin Suhri Kasim (Jurnal Neo Societal, 2026)
This article aims to analyze gender inequality in marine resource management in coastal communities by highlighting power relations, gender-based division of labor, and women's access and control over productive resources. The research draws on feminist political economy perspectives and institutional theory to explain how cultural norms, social structures, and marine policies affect the position of women in fisheries activities and coastal economies. The research method uses a qualitative approach through in-depth interviews, focus group discussions, and participatory observation of women fishermen, seafood processors, and micro business actors in coastal areas. The findings of the study show that women have an important role in the fisheries economic chain, especially in processing activities, marketing of marine products, and household financial management. However, these contributions are often not recognized in local policies and institutions. Women also face barriers to access productive assets, fishing technology, venture capital, and decision-making space, thereby strengthening their economic and political marginalization. In addition, gender-biased division of labor still places women in vulnerable domestic and informal sector jobs without adequate social protection. On the other hand, coastal women are developing a range of collective strategies through social networks, joint venture groups, and community solidarity to expand their participation in the management of marine resources. This study concludes that fair and sustainable governance of marine resources requires gender-responsive marine policies, strengthening women's institutions, and expanding access to economic resources and decision-making.